Evaluation of Enzyme-Linked Immunosorbent Assay Using Recombinant 56-kDa Type-Specific Antigens Derived from Multiple Orientia tsutsugamushi Strains for Detection of Scrub Typhus Infection - Yang, Su-Lin (Am J Trop Med Hyg, 2019)
Scrub typhus is caused by the intracellular bacterium Orientia tsutsugamushi. The 56-kDa type-specific antigen (TSA) displays a significant antigenic variation across different O. tsutsugamushi strains. To minimize the influence of the antigenic diversity of TSA on assay sensitivity, we developed a mixed-TSA enzyme-linked immunosorbent assay (mixed-TSA ELISA) using a mixture of recombinant TSAs of prototype (Karp, Gilliam, and Kato) and local (TW-1, TW-10, TW-19, and TW-22) O. tsutsugamushi strains as antigens to detect immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies against O. tsutsugamushi. These four local strains covered a major part of the total genetic diversity of TSA gene of O. tsutsugamushi in Taiwan. A total of 109 acute-phase serum samples from O. tsutsugamushi polymerase chain reaction–positive, scrub typhus patients, and 82 negative control serum samples from non-scrub typhus cases were used for evaluation of the recombinant TSA-based ELISA. We compared the performance of the mixed-TSA ELISA with immunofluorescence assay (IFA), which is considered the gold standard method for the serological diagnosis of scrub typhus. The results indicated that the sensitivity of IgM mixed-TSA ELISA (80.7%) was significantly higher than that of IgM IFA (68.8%). We demonstrated that the mixed-TSA ELISA had a high sensitivity and specificity and can be used for screening of scrub typhus patient in the early phase of the disease.